Predictors of worsening food security among women living with and without HIV and seronegative women during COVID-19: a mixed methods study - Jenni M. Wise; Hilary Bethancourt; Torsten B. Neilands; Anna Leddy; Gypsyamber D’Souza; Mirjam-Colette Kempf; Janet M. Turan; Gina Wingood; M. Reuel Friedman; Jennafer Kwait; Lakshmi Goparaju; Mardge Cohen; et al. (Food Security, 2026)
This study aimed to assess the prevalence, severity, predictors, and lived experiences of food insecurity among women enrolled in the Women’s Interagency HIV Study in the USA in 2020, at the height of the COVID-19 pandemic. We hypothesized that pre-existing socioeconomic and health-related disparities would heighten the risk of worsening food insecurity during the pandemic. The 10-item US Household Food Security Survey was administered to participants three times between June and September 2020. Multilevel mixed-effects ordered logistic regression models were used to estimate the odds of worsening food security compared to pre-pandemic baseline data. Qualitative interviews were conducted among a subset of participants to add understanding of the lived experience of food insecurity during the pandemic, beyond what quantitative measures could provide. Among 1,506 women, 28% had marginal to very low food security at baseline, and between 13.6-17.3% experienced worsening food security during pandemic measures. Women with household incomes <$12,000/year were particularly vulnerable to worsening food insecurity, including those experiencing unemployment (OR: 2.06, 95% CI:1.36, 3.13), job loss (OR: 1.47, 95% CI: 1.04-2.06), loss of financial support (OR: 1.91,95% CI: 1.23, 2.97), and those with reduced access to usual sources of food (OR: 7.67, 95% CI:4.78, 12.30). While the quantitative data suggest that relatively few women experienced worsening food security during the pandemic, the qualitative data suggest that many more women had difficulty accessing preferred and healthy foods and experienced disruption to social services, which typically facilitate the ability to access food. Women described how informal social systems (e.g., neighborhood gardens, sharing resources) bridged the gap left by more formal systems during this time. Taken together, these findings suggest that women with pre-existing socioeconomic vulnerability were disproportionately and negatively impacted by the social and economic disruptions of the COVID-19 pandemic. Interventions are needed to address structural vulnerabilities, improve safeguards to food security during times of distress, and harness the capacity of community-based support systems.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

MSH6-proficient crypt foci in MSH6 constitutional mismatch repair deficiency: reversion of a frameshifted coding microsatellite to its wild-type sequence - Jinru Shia; Francisco Sanchez-Vega; Stanley Cho; Jie-Fu Chen; Chin-Tung Chen; Umesh Bhanot; Nil Urganci; Canan Firat; Peter Ntiamoah; Raymond A. Isidro; Amitabh Srivastava; Martin R. Weiser; et al. (Familial Cancer, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Deep learning with simulated laser scanning data for 3D point cloud classification - Alberto M. Esmorís; Hannah Weiser; Lukas Winiwarter; Jose C. Cabaleiro; Bernhard Höfle (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Mammalian organ regeneration in spiny mice - Daryl M. Okamura; Elizabeth D. Nguyen; Sarah J. Collins; Kevin Yoon; Joshua B. Gere; Mary C. M. Weiser-Evans; David R. Beier; Mark W. Majesky (Journal of Muscle Research and Cell Motility, 2023)

Teaching Tissue Repair Through an Inquiry-Based Learning Bioadhesives Module - Christopher J. Panebianco; Poorna Dutta; Jillian R. Frost; Angela Huang; Olivia S. Kim; James C. Iatridis; Andrea J. Vernengo; Jennifer R. Weiser (Biomedical Engineering Education, 2023)

Selection of Relevant Bacterial Strains for Novel Therapeutic Testing: a Guidance Document for Priority Cystic Fibrosis Lung Pathogens - Eshwar Mahenthiralingam; Rebecca Weiser; R. Andres Floto; Jane C. Davies; Joanne L. Fothergill (Current Clinical Microbiology Reports, 2022)
Purpose of Review People with cystic fibrosis (CF) suffer chronic lung infections with a range of antimicrobial-resistant bacterial pathogens. There is an urgent need for researchers to develop novel anti-infectives to treat these problematic infections, but how can we select bacterial strains which are relevant for robust testing and comparative research? Recent Findings Pseudomonas aeruginosa , Burkholderia cepacia complex and Burkholderia gladioli , Mycobacterium abscessus complex, Staphylococcus aureus, Haemophilus influenza, and several multidrug-resistant Gram-negative species were selected as key CF infections that urgently require new therapeutics. Reference isolates and strain panels were identified, and a summary of the known genotypic diversity of each pathogen was provided. Summary Here, we summarise the current strain resources available for priority CF bacterial pathogens and highlight systematic selection criteria that researchers can use to select strains for use in therapeutic testing.

Progress toward liquid biopsies in pediatric solid tumors - Daniel A. Weiser; Diana C. West-Szymanski; Ellen Fraint; Shoshana Weiner; Marco A. Rivas; Carolyn W.T. Zhao; Chuan He; Mark A. Applebaum (Cancer and Metastasis Reviews, 2019)

The Journey to AAPS 2020: a Reflection from Strategic Planning to PharmSci 360 - Joseph W. Polli; Christopher R. McCurdy; Dale Eric Wurster; Binodh S. DeSilva; Annette Bak; Reina Bendayan; Bernd Meibohm; Allen C. Templeton; William Weiser (The AAPS Journal, 2019)

The Journey to AAPS 2020: a Reflection from Strategic Planning to PharmSci 360 - Joseph W. Polli; Christopher R. McCurdy; Dale Eric Wurster; Binodh S. DeSilva; Annette Bak; Reina Bendayan; Bernd Meibohm; Allen C. Templeton; William Weiser (AAPS PharmSciTech, 2018)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Applying Transcranial Magnetic Stimulation (TMS) Over the Dorsal Visual Pathway Induces Schizophrenia-like Disruption of Perceptual Closure - Revital Amiaz; Dana Vainiger; Ari A. Gershon; Mark Weiser; Michal Lavidor; Daniel C. Javitt (Brain Topography, 2016)

CD4 T cell knockout does not protect against kidney injury and worsens cancer - Kameswaran Ravichandran; Qian Wang; Abdullah Ozkok; Alkesh Jani; Howard Li; Zhibin He; Danica Ljubanovic; Mary C. Weiser-Evans; Raphael A. Nemenoff; Charles L. Edelstein (Journal of Molecular Medicine, 2016)

Mismatch repair deficient-crypts in non-neoplastic colonic mucosa in Lynch syndrome: insights from an illustrative case - Jinru Shia; Zsofia K. Stadler; Martin R. Weiser; Efsevia Vakiani; Robin Mendelsohn; Arnold J. Markowitz; Moshe Shike; C. Richard Boland; David S. Klimstra (Familial Cancer, 2015)

The biogeography and filtering of woody plant functional diversity in North and South America - Nathan G. Swenson; Brian J. Enquist; Jason Pither; Andrew J. Kerkhoff; Brad Boyle; Michael D. Weiser; James J. Elser; William F. Fagan; Jimena Forero‐Montaña; Nikolaos Fyllas; Nathan J. B. Kraft; Jeffrey K. Lake; et al. (Global Ecology and Biogeography, 2012)
Aim In recent years evidence has accumulated that plant species are differentially sorted from regional assemblages into local assemblages along local‐scale environmental gradients on the basis of their function and abiotic filtering. The favourability hypothesis in biogeography proposes that in climatically difficult regions abiotic filtering should produce a regional assemblage that is less functionally diverse than that expected given the species richness and the global pool of traits. Thus it seems likely that differential filtering of plant traits along local‐scale gradients may scale up to explain the distribution, diversity and filtering of plant traits in regional‐scale assemblages across continents. The present work aims to address this prediction. Location North and South America. Methods We combine a dataset comprising over 5.5 million georeferenced plant occurrence records with several large plant functional trait databases in order to: (1) quantify how several critical traits associated with plant performance and ecology vary across environmental gradients; and (2) provide the first test of whether the woody plants found within 1° and 5° map grid cells are more or less functionally diverse than expected, given their species richness, across broad gradients. Results The results show that, for many of the traits studied, the overall distribution of functional traits in tropical regions often exceeds the expectations of random sampling given the species richness. Conversely, temperate regions often had narrower functional trait distributions than their smaller species pools would suggest. Main conclusion The results show that the overall distribution of function does increase towards the equator, but the functional diversity within regional‐scale tropical assemblages is higher than that expected given their species richness. These results are consistent with the hypothesis that abiotic filtering constrains the overall distribution of function in temperate assemblages, but tropical assemblages are not as tightly constrained.

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Retroviral insertions in the VISION database identify molecular pathways in mouse lymphoid leukemia and lymphoma - Keith C. Weiser; Bin Liu; Gwenn M. Hansen; Darlene Skapura; Kathryn E. Hentges; Sujatha Yarlagadda; Herbert C. Morse III; Monica J. Justice (Mammalian Genome, 2007)

Plant Cold Acclimation: The Role of Abscisic Acid - L. V. Gusta; R. Trischuk; C. J. Weiser (Journal of Plant Growth Regulation, 2005)

18th International Mouse Genome Conference - Amy C. Lossie; Thomas P. Meehan; Andrew Castillo; Lihua Zheng; Keith C. Weiser; Mark A. Strivens; Monica J. Justice (Mammalian Genome, 2005)

Characterization of the anticonvulsant and neuroprotectant BIIR 561 CL in vitro: effects on native and recombinant α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors - T. Weiser; M. Iizuka; S. Nishimura; I. Akiba; E. Barsoumian; M. Zhou; C. Steinhäuser; M. Brenner; R. Palluk; M. Wienrich (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Improving potato protein I. Evaluation of selection techniques - S. L. Desborough; C. J. Weiser (American Journal of Potato Research, 1974)

Protein comparisons in selected Phureja-haploid Tuberosum families - Sharon Desborough; C. J. Weiser (American Journal of Potato Research, 1972)